John W. Persons correspondence - Persons, John W.
ALS (1845 July 31) written by Persons, while on a voyage in an unnamed whaling ship, to his brother, William B. Persons, of West Randolph, Vt. Person indicates that the ship called at several islands in the Azores, caught a sperm whale, and was scheduled to continue on to a number of islands in the Pacific Ocean.
Whaler.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Persons, William B. -- Correspondence; Whaling -- Atlantic Ocean; Whaling -- Azores; Whaling -- Pacific Ocean; Whalers (Persons)